2020
DOI: 10.3389/fnint.2020.00031
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Imaging Studies in the Combined and Inattentive Subtypes of Attention Deficit Hyperactivity Disorder

Abstract: Insights to underlying neural mechanisms in attention deficit hyperactivity disorder (ADHD) have emerged from neuroimaging research; however, the neural mechanisms that distinguish ADHD subtypes remain inconclusive. Method: We reviewed 19 studies integrating magnetic resonance imaging [MRI; structural (sMRI), diffusion, functional MRI (fMRI)] findings into a framework exploring pathophysiological mechanisms underlying the combined (ADHD-C) and predominantly inattentive (ADHD-I) ADHD subtypes. Results: Despite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 106 publications
3
46
0
5
Order By: Relevance
“…Fall and colleagues [ 49 ] indirectly support these findings reporting mean reaction times correlated with MD values in the striatum and thalamus in ADHD-C compared to controls. Interestingly, these results are consistent with studies using structural gray matter and resting state functional connectivity, reported in a recent review [ 50 ] which have shown disruptions in the motor network in ADHD-C. Whether these structural connectivity disruptions or the absence of WM abnormalities attribute to functional deficits associated with the subtypes of ADHD, remain unconfirmed.…”
Section: Discussionsupporting
confidence: 91%
“…Fall and colleagues [ 49 ] indirectly support these findings reporting mean reaction times correlated with MD values in the striatum and thalamus in ADHD-C compared to controls. Interestingly, these results are consistent with studies using structural gray matter and resting state functional connectivity, reported in a recent review [ 50 ] which have shown disruptions in the motor network in ADHD-C. Whether these structural connectivity disruptions or the absence of WM abnormalities attribute to functional deficits associated with the subtypes of ADHD, remain unconfirmed.…”
Section: Discussionsupporting
confidence: 91%
“…There is a vast collection of extant literature on neurobiological correlates of ADHD that could ultimately inform a precision medicine approach [ 13 , 14 ]. In this review, we focus on deficient fronto-striatal connectivity driven by atypical balance of neural excitation and inhibition (E/I).…”
Section: Introduction: Need For Precision Medicine Care In Adhdmentioning
confidence: 99%
“…Furthermore, structural and functional imaging studies have shown evidence of altered brain volumes in ADHD leading to dysfunction in fronto-subcortical pathways [ 11 ]. A recent fMRI study noted that the altered connectivity in the cerebellar network was present in the combined type of ADHD (inattentive and hyperactive) as compared with alterations in the cingulo-frontoparietal attention and visual networks found in the predominately inattentive subtype [ 16 ].…”
Section: Discussionmentioning
confidence: 99%